INDIVIDUAL COUNSELING USING EXPRESSION CARDS TO CHANGE THE PERSONALITY OF AN INTROVERT INDIVIDUAL STUDENT INTO AN EXTROVERT - Pramono, Sidik (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to understand in depth how expression cards can help introverted physically disabled students develop their self-expression and social interaction skills during individual counseling sessions. The study specifically explores the experiences, perceptions, and changes felt by physically disabled students during the counseling process using expression cards. The scope of this study includes exploring the process of interaction between physically disabled students and expression cards, dynamics during counseling sessions, and changes felt in the context of students' social and emotional relationships. The method used is a qualitative approach with a case study design, data were collected through in-depth interviews with physically disabled students and counselors, participant observation during counseling sessions, and reflective analysis of student narratives. Data analysis was carried out thematically to find patterns and meanings from students' experiences. The results showed that expression cards provide space for introverted physically disabled students to express their feelings indirectly, thus helping them feel more comfortable in communicating. Physically disabled students reported that expression cards made it easier for them to understand and convey emotions that were difficult to express verbally. In addition, individual counseling sessions with this tool created an environment that supported students' social interactions with classmates. It is concluded that expression cards are effective as a counseling tool to help introvert students develop social and emotional skills. The interaction process facilitated by these cards has a positive impact on students' openness and self-confidence in interacting. This study recommends the development of similar media that are more adaptive to the needs of individuals with disabilities to support successful counseling.